Hubungan Pola Asuh Orang Tua Dengan Kejadian Speech Delay Pada Anak Prasekolah Usia 3-6 Tahun Di Wilayah Kerja Puskesmas Dadok Tunggul Hitam Kota Padang - Sisila Kencana; Sari Indah Kesuma; Rischa Hamdanesti (CV. ITTC INDONESIA, 2026)
Speech delay in preschool children is a developmental problem that can hinder communication, social interaction, and academic readiness in the future. The prevalence of speech delay is reported to be relatively high both globally and in Indonesia, with various risk factors such as genetics, nutritional status, excessive use of gadgets, and parenting style. This study aimed to determine the relationship between parenting styles and the incidence of speech delay among preschool children aged 3–6 years in the working area of Dadok Tunggul Hitam Health Center, Padang City. This study employed a quantitative method with a cross-sectional design. The population consisted of 69 children, and a sample of 41 children was selected using purposive sampling according to the inclusion criteria. The independent variable was parenting style, while the dependent variable was the incidence of speech delay. Data were collected using a parenting style questionnaire and a language development assessment based on a modified Denver II test. Data analysis was carried out using univariate and bivariate approaches with the Chi-Square test. The results showed that the authoritarian parenting style was most commonly applied (48.8%), The incidence of speech delay was found in 53.7% of children. The Chi-Square test obtained a p-value of 0.000 (p < 0.05), indicating a significant relationship between parenting style and the incidence of speech delay. The democratic parenting style was proven to better support language development compared to authoritarian and permissive styles. In conclusion, appropriate parenting, particularly the democratic style that emphasizes communication and stimulation, plays an important role in preventing speech delay. It is recommended that parents increase verbal interaction, limit gadget use, and actively provide early language stimulation.